Gender Bias, Social Impact Framing, and Evaluation of Entrepreneurial Ventures - Lee, Matthew; Huang, Laura (Organization Science, 2018)
Recent studies find that female-led ventures are penalized relative to male-led ventures as a result of role incongruity or a perceived “lack of fit” between female stereotypes and expected personal qualities of business entrepreneurs. We examine whether social impact framing that emphasizes a venture’s social–environmental welfare benefits, which research has shown to elicit stereotypically feminine attributions of warmth, diminishes these penalties. We initially investigate this proposition in a field study of evaluations of early-stage ventures and find evidence of lessened gender penalties for female-led ventures that are presented using a social impact frame. In a second study, we experimentally validate this effect and show that it is mediated by the effect of social impact framing on perceptions of the entrepreneur’s warmth. The effect of social impact frames on venture evaluations did not apply to men, was not a result of perceptions of increased competence, and was not conditional on the gender of evaluators. Taken together, our findings demonstrate that social impact framing increases attributions of warmth for all entrepreneurs but with positive consequences on business evaluation only for female-led ventures, for which increased perceptions of warmth attenuate female entrepreneurs’ gender role incongruity. The online appendix is available at https://doi.org/10.1287/orsc.2017.1172 .